2000
DOI: 10.1038/sj.onc.1203323
|View full text |Cite
|
Sign up to set email alerts
|

Ras protein is involved in the physiological regulation of phospholipase D by platelet derived growth factor

Abstract: Lipid-derived metabolites play an important role in the regulation of cell responses to external stimuli, including cell growth control, transformation and apoptosis. Phospholipase D (PLD) is one of the critical elements in the regulation of lipid metabolism and the generation of second messengers, some of them involved in cell growth control. Oncogenic Ras proteins aect the activity of PLD by two alternate mechanisms, involving a positive activation and a feedback negative loop. Here we investigate the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
1
15
1
Order By: Relevance
“…Although there is abundant information demonstrating activation of PLD by mitogenic stimulation of cells by growth factors, its involvement in the regulation of cell growth is not fully understood. Recently it has been demonstrated that Ras proteins are involved in the physiological regulation of PLD by PDGF (Lucas et al, 2000). On the other hand, PLD has been implicated in the acquisition of the transforming potential of murine ®broblasts (Lu et al, 2000) or the invasive capacity of transformed cells (Imamura et al, 1993) one of the most important determinants of malignant behavior (Herna ndez-Alcoceba et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is abundant information demonstrating activation of PLD by mitogenic stimulation of cells by growth factors, its involvement in the regulation of cell growth is not fully understood. Recently it has been demonstrated that Ras proteins are involved in the physiological regulation of PLD by PDGF (Lucas et al, 2000). On the other hand, PLD has been implicated in the acquisition of the transforming potential of murine ®broblasts (Lu et al, 2000) or the invasive capacity of transformed cells (Imamura et al, 1993) one of the most important determinants of malignant behavior (Herna ndez-Alcoceba et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PLD and PI3K are regulated by receptor tyrosine kinases. Similar to PI3K, PLD is regulated by RalA, a downstream target of Ras, in plateletderived growth factor-and epidermal growth factor-stimulated cells (49,50), and PLD2 is tyrosine-phosphorylated by forming a physical complex with the epidermal growth factor receptor (51). Recent studies have demonstrated that PLD1 and PI3K play a role in GLUT4 translocation between the plasma membranes and intracellular vesicles in insulin-stimulated cells (52).…”
Section: S1p-induced Phospholipase D Activation In Edg3-over-expressimentioning
confidence: 99%
“…Remarkably, CO and exogenous compounds such as 3-(5 0 -hydroxymethyl-2 0 -furyl)-1-benzylindazole (YC-1) and 3-(4-amino-5-cyclopropylpyrimidin-2-yl)-1-(2-fluorobenzyl)-1H-pyradazolo [3,4-b]pyridine (BAY 41-2272) synergistically activate sGC to levels approximately similar to those induced by NO [88,89]. Such sGC induction leads to the increase of the cGMP level and to the activation of the cGMP-dependent protein kinase (PKG) phospho-transferase activity, thus affecting several cellular functions based on ion channel, phosphodiesterase, and protein kinase actions [77,80,[90][91][92][93][94][95].…”
Section: Co Signalingmentioning
confidence: 99%